Psychological Traits and Behavioural Influences in Patients with Dystonia—An Observational Cohort Study in a Romanian Neurology Department - Davidescu, Eugenia Irene (Life (Basel), 2021)
(1) Background: Emerging evidence indicates that non-motor symptoms significantly influence the quality of life in dystonic patients. Therefore, it is essential to evaluate their psychological characteristics and personality traits. (2) Methods: Subjects with idiopathic dystonia and a matched control group were enrolled in this prospective observational cohort study. Inclusion criteria for patient group included idiopathic dystonia diagnosis, evolution exceeding 1 year, and signed informed consent. Inclusion criteria for the control group included lack of neurological comorbidities and signed informed consent. All subjects completed the DECAS Personality Inventory along with an additional form of demographic factors. Data (including descriptive statistics and univariate and multivariate analysis) were analyzed with SPSS. (3) Results: In total, 95 participants were included, of which 57 were in the patient group. Females prevailed (80%), and the mean age was 54.64 ± 12.8 years. The most frequent clinical features of dystonia were focal distribution (71.9%) and progressive disease course (94.73%). The patients underwent regular treatment with botulinum toxin (85.95%). In addition, patients with dystonia obtained significantly higher openness scores than controls, even after adjusting for possible confounders (p = 0.006). Personality traits were also different between the two groups, with patients more often being fantasists (p = 0.007), experimenters (p = 0.022), sophists (p = 0.040), seldom acceptors (p = 0.022), and pragmatics (p = 0.022) than control subjects. (4) Conclusion: Dystonic patients tend to have different personality profiles compared to control subjects, which should be taken into consideration by the treating neurologist.